ChemInform Abstract: Alloys in Catalysis: Phase Separation and Surface Segregation Phenomena in Response to the Reactive Environment. Issue 6 (20th February 2013) - Zafeiratos, Spiros; Piccinin, Simone; Teschner, Detre
Abstract Review: 120 refs.